2013
DOI: 10.1007/s11256-013-0239-4
|View full text |Cite
|
Sign up to set email alerts
|

Key Elements of a Successful Multi-System Collaboration for School-Based Mental Health: In-Depth Interviews with District and Agency Administrators

Abstract: The alarming number of youth with unmet mental health needs in the US is a significant social problem. The pilot school-based mental health project described here established an innovative multi-system partnership between an urban school district, a public mental health agency, and a local university to better meet the mental health needs of youth in one community. This qualitative study employed in depth interviews with six key administrators who were instrumental in developing and executing the project to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Crisis response models involving police identified in our review strongly emphasized relationship-building between law enforcement officers, students, and parents; a prevention and education role; and involving officers in student education (Daniels et al, 2007;Derzon et al, 2012;Heinen et al, 2006;James et al, 2011;Moriarty et al, 1993). These case reports are consistent with prior research indicating that strong schoolcommunity partnerships tend to be characterized by relationships among leaders, communication around barriers, commitment to quality improvement, and understanding the community and social context (Powers et al, 2013;Weist & Evans, 2005;Weist et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…Crisis response models involving police identified in our review strongly emphasized relationship-building between law enforcement officers, students, and parents; a prevention and education role; and involving officers in student education (Daniels et al, 2007;Derzon et al, 2012;Heinen et al, 2006;James et al, 2011;Moriarty et al, 1993). These case reports are consistent with prior research indicating that strong schoolcommunity partnerships tend to be characterized by relationships among leaders, communication around barriers, commitment to quality improvement, and understanding the community and social context (Powers et al, 2013;Weist & Evans, 2005;Weist et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…Limited transportation, stigma associated with mental health, lack of finances, and restricted number of services are some of the possible barriers to children living at low SES levels receiving psychological services (Gamble & Lambros, 2014). SBFC services are a good option to help mediate some of the known barriers of families and children accessing mental health resources (Powers et al, 2013). Although family systems approaches have been shown to be effective with children in vulnerable populations, there is a lack of research and focus on SBFC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has sought to elucidate stakeholder perspectives on potential benefits of partnerships between community MH organizations and schools to expand MH services offered in school settings, as well as challenges that may occur when implementing these partnerships (Blackman et al, 2016 ; Mellin & Weist, 2011 ; Mellin et al, 2017 ; Powers et al, 2013 ). In a survey of 384 teachers, Mellin et al ( 2017 ) identified several perceived benefits of these collaborative relationships; these perceived benefits included increased support for teachers to address student MH needs, increased MH programming available for students, improved MH care access for students and families, and improved family-school relationships (Mellin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of 384 teachers, Mellin et al ( 2017 ) identified several perceived benefits of these collaborative relationships; these perceived benefits included increased support for teachers to address student MH needs, increased MH programming available for students, improved MH care access for students and families, and improved family-school relationships (Mellin et al, 2017 ). To inform potential challenges associated with these collaborative relationships, two studies of specific programs collected qualitative data from school leaders and stakeholders from MH agencies (Mellin & Weist, 2011 ; Powers et al, 2013 ). Reported challenges from stakeholders included: siloed systems in which schools and MH agencies have different language concerning MH and different missions (Powers et al, 2013 ); resistance to MH services delivered by MH agencies due to misunderstanding about student MH challenges and stigma related to MH (Powers et al, 2013 ); lack of role clarity of different stakeholders participating in the partnership (Mellin & Weist, 2011 ); and lack of buy-in from school professionals when MH services are delivered by community-based clinicians (Mellin & Weist, 2011 ).…”
Section: Introductionmentioning
confidence: 99%